A physical association between the human mutY homolog (hMYH) and DNA topoisomerase II-binding protein 1 (hTopBP1) regulates Chk1-induced cell cycle arrest in HEK293 cells - Han, Se Hee; Hahm, Soo-Hyun; An Hue Vy Tran; Chung, Ji Hyung; Hong, Myoung-Ki; Paik, Hyun-Dong; Kim, Key-Sun; Han, Ye Sun (BIOMED CENTRAL LTD, 2015)
Background: Human DNA topoisomerase II-binding protein 1 (hTopBP1) plays an important role in DNA replication and the DNA damage checkpoint pathway. The human mutY homolog (hMYH) is a base excision repair DNA glycosylase that excises adenines or 2-hydroxyadenines that are mispaired with guanine or 7,8-dihydro-8-oxoguanine (8-oxoG). hTopBP1 and hMYH were involved in ATR-mediated Chk1 activation, moreover, both of them were associated with ATR and hRad9 which known as checkpoint-involved proteins. Therefore, we investigated whether hTopBP1 interacted with hMYH, and what the function of their interaction is. Results: We documented the interaction between hTopBP1 and hMYH and showed that this interaction increased in a hydroxyurea-dependent manner. We also mapped the hMYH-interacting region of hTopBP1 (residues 444-991). In addition, we investigated several cell cycle-related proteins and found that co-knockdown of hTopBP1 and hMYH significantly diminished cell cycle arrest due to compromised checkpoint kinase 1 (Chk1) activation. Moreover, we observed that hMYH was essential for the accumulation of hTopBP1 on damaged DNA, where hTopBP1 interacts with hRad9, a component of the Rad9-Hus1-Rad1 complex. The accumulation of hTopBP1 on chromatin and its subsequent interaction with hRad9 lead to cell cycle arrest, a process mediated by Chk1 phosphorylation and ataxia telangiectasia and Rad3-related protein (ATR) activation. Conclusions: Our results suggested that hMYH is necessary for the accumulation of hTopBP1 to DNA damage lesion to induce the association of hTopBP1 with 9-1-1 and that the interaction between hMYH and hTopBP1 is essential for Chk1 activation. Therefore, we suggest that the interaction between hMYH and hTopBP1 is crucial for activation of the ATR-mediated cell cycle checkpoint.